Staudinger ligation towards cyclodextrin dimers in aqueous/organic media. Synthesis, conformations and guest-encapsulation ability - Manouilidou, Malamatenia D.; Lazarou, Yannis G.; Mavridis, Irene M.; Yannakopoulou, Konstantina (Beilstein Journal of Organic Chemistry, 2014)
β-Cyclodextrin (β-CD) dimers have been prepared using the bioorthogonal Staudinger ligation for the first time. In addition to a known linker, methyl 2-(diphenylphosphanyl)terephthalate, a doubly active linker was specifically developed that enabled connection of two β-CD units in a single step and in aqueous/organic media, under mild conditions and with good yields. A three-carbon spacer between the β-CD torus and the azido group was required for facile dimer formation. The products, as studied by NMR spectroscopy, were found to adopt closed conformations by intramolecular self-inclusion. On the other hand, association via intermolecular binding was also observed in aqueous solution, confirmed by DOSY NMR experiments. Despite self-inclusion, the β-CD cavities were capable of guest encapsulation, as shown by titration experiments: the binding constant with 1-adamantylamine was similar to that of natural β-CD. Theoretical calculations for isolated molecules (PM3 level of theory) and in the presence of solvent [water, PM3(COSMO)] as well as DFT calculations suggested that the compounds prefer to adopt conformations which bring the phenyl groups either inside the β-CD cavity (inclusion) or over its narrow side (vicinal). Thus, Staudinger ligation could be the method of choice for linking CDs exhibiting (i) ease of preparation in aqueous media, in short steps, under mild conditions and in good yields, (ii) satisfactory aqueous solubility and independent binding capacity of the cavities.
Keywords: calculations; conformations; cyclodextrin; dimer; inclusion; PM3; Staudinger ligation